News from the new American diaspora and other tales of exile - Neugeboren, Jay (Literary modernism series., 2005)
Prize-winning novelist Jay Neugeboren's third collection of short stories focuses on Jews in various states of exile and expatriation - strangers in strange lands, far from home. These dozen tales, by an author whose stories have been selected for more than fifty anthologies, including Best American Short Stories and O. Henry Prize Stories, span the twentieth century and vividly capture brief moments in the lives of their characters: a rabbi in a small town in New England struggling to tend to his congregation and himself, retirees who live in Florida but dream of Brooklyn, a boy at a summer camp in upstate New York learning about the Holocaust for the first time, Russians living in Massachusetts with the family who helped them immigrate. In "The Other End of the World," an American soldier who has survived life in a Japanese prisoner of war camp grieves for members of his family murdered in a Nazi death camp, and in "Poppa's Books" a young boy learns to share his father's passion for the rare books that represent the Old World. "This Third Life" tells of a divorced woman who travels across Germany searching for new meaning in her life after her children leave home, while both "His Violin" and "The Golden Years" explore the plight of elderly Jews, displaced from New York City to retirement communities in Florida, who struggle with memory, madness, and mortality. Set in various times and places, these poignant stories are all tales of personal exile that also illuminate that greater diaspora - geographical, emotional, or spiritual - in which many of us, whether Jews or non-Jews, live.